Flotation techniques (FLOTAC and mini-FLOTAC) for detecting gastrointestinal parasites in howler monkeys. Issue 1 (December 2017) - Alvarado-Villalobos, Mayra; Cringoli, Giuseppe; Maurelli, Maria; Cambou, Aurelie; Rinaldi, Laura; Barbachano-Guerrero, Arturo; Guevara, Roger; Chapman, Colin; Serio-Silva, Juan
Abstract Background Analyses of environmental correlates of the composition of gastrointestinal parasite communities in black howler monkeys (Alouatta pigra ) have been hindered by inadequate calibration techniques of detection and quantification methods of the parasites. Here we calibrate samples and compare the likelihood of parasite detection using two flotation techniques, FLOTAC and Mini-FLOTAC, and compare flotation solution, preservation method and dilution ratio for egg detection and counts of the most common parasites (Controrchis spp. andTrypanoxyuris spp.) in howler monkeys. Results For samples preserved in 5% formalin, the Mini-FLOTAC technique was the best option for qualitative and quantitative copro-microscopic analysis. This technique displays an 83.3% and 100% detection ofControrchis spp. andTrypanoxyuris spp. infections, respectively. For the trematodeControrchis spp., more eggs per gram of feces (EPG) were recorded with the flotation solution (FS) #7 (zinc sulfate; specific gravity SG = 1.35) at 1:20 and 1:25 dilution than other methods. By contrast, for the nematodeTrypanoxyuris spp., the best results were recorded with FS1 (sucrose and formaldehyde; SG = 1.20) at 1:10 dilution. Conclusions We recommend the Mini-FLOTAC technique for general use with parasite analysis on frugivore/folivores like the howler monkey, especially if many samples are analyzed. The technique has a high detection rate and the best EPG counts, allowing the qualitative and quantitative analysis of parasite load among the species or populations without the need for specialized equipment.